Manufacturing of a maxillofacial prosthesis from an axial tomography using simulation technologies with a virtual machine tool and four-axis machining (2016)
The surfaces of a personalized maxillofacial prosthesis were manufactured in a relatively short time with moderate cost. The topography of the surface was generated with a Computer-Aided Design system from a Computerized Axial Tomography of a maxillofacial area. The design of the machining manufacturing process, its simulation and verification were facilitated by the use of a virtual machine tool equivalent to the real machine tool available. Finally, the manufacturing process was successfully achieved by using a conventional 3-axis vertical machining center equipped with a fourth external rotational axis. Using a 3-axis machine tool with an additional axis is less expensive than using a 5-axis machine. There is abundant literature about machining of free-form surfaces using a 5-axis machine tool, but there are few precedents for the manufacturing of this kind of surface using a 4-axis machine.